Syzygium cumini seed extract ameliorates HCHF-induced obesity in rat model by modulating lipogenic and adipocytogenic gene expression - Shilpa Maji; Angshita Ghosh; Sandip Chattopadhyay; Arindam Dey (Elsevier, 2024)
Objective: The present investigation was aimed to explore an oral treatment strategy for high-carbohydrate-high-fat (HCHF)-diet induced obesity using hydromethanolic extract of Syzygium cumini (SCM) seeds. Methods: SCM at a dose of 100 mg /kg body weight was administered to the HCHF-diet-fed obese rats for 4 weeks. The effects of SCM on body weight and lipid profiles were analysed. Electrozymographic and enzymatic antioxidant status were investigated by the native gel technique and spectrophotometric assay. The levels of serum leptin, ghrelin, adiponectin, insulin, IL-6 and TNF-α were assessed by ELISA. Lipogenic and adipocytogenic gene expression was determined by PCR. Results: SCM-treatment significantly decreased the body weight and hepato-reno somatic index as compared with HCHF-fed group. SCM partially normalized the HCHF-induced altered liver enzymes, lipid profile and hyperinsulinemia. SCM also improved the serum adipokines level (adiponectin, leptin and ghrelin) and partially restored the hepato-renal and adipose tissue histomorphology. Downregulation of the expressions of different lipogenic and adipocytogenic genes was also documented following coadministration of SCM extract. Conclusion: These results suggest that SCM could be a potential therapeutic for the management of obesity-induced by the HCHF-diet.